Differentiation of Human Adipose Tissue Derived Mesenchymal Stem Cells to Functional Hepatocytes like Cells: Exploring the Niche and Admscs Conditioned Media - Sultana, Rasia; Bhatt, Anugya (Archives of Clinical and Biomedical Research, 2021)
Tissue engineered approaches have been used for hepatic regeneration and growing hepatic cells in-vitro, however it remains challenging due to the lesser proliferative capacity of the hepatic cells as well as cell source availability due to damaged tissues. Stem cells could be an alternative strategy if differentiated to functional hepatic like cells by providing suitable niche or culture conditions. In the present study we tried to explore differentiation of mesodermal origin cells to the endodermal origin hepatic cells under different culture conditions including fibrin niche and adipocytes derived mesenchymal stem cells conditioned medium. Fibrin provides better cell adhesion and proliferation. Mesenchymal stem cells were isolated and characterized. Two step induction was used for differentiating into hepatic like cells. Functionality of the differentiated hepatic like cells was analyzed using Cyto P 450, glycogen storage and urea/albumin assay at different time points. It was observed the fibrin niche supports the hepatic differentiation and differentiated cells shows hepatic functions. This approach may be used to generate alternative cell source for hepatic tissue engineering.